The world map 1300-1492 the persistence of tradition and transformation - Edson, Evelyn (Johns Hopkins Univ. Press, 2007)
In the two centuries before Columbus, mapmaking was transformed. The World Map, 1300-1492 investigates this important, transitional period of mapmaking. Beginning with a 1436 atlas of ten maps produced by Venetian Andrea Bianco, Evelyn Edson uses maps of the fourteenth and fifteenth centuries to examine how the discoveries of missionaries and merchants affected the content and configuration of world maps. She finds that both the makers and users of maps struggled with changes brought about by technological innovation₇the compass, quadrant, and astrolabe₇rediscovery of classical mapmaking approaches, and increased travel. To reconcile the tensions between the conservative and progressive worldviews, mapmakers used a careful blend of the old and the new to depict a world that was changing₇and growing₇before their eyes. This engaging and informative study reveals how the ingenuity, creativity, and adaptability of these craftsmen helped pave the way for an age of discovery.
Includes bibliographical references and index
Keywords: Geschichte 1400-1500; Geschichte 1300-1500; Geschichte 1300-1492; Wereldkaarten; Geografie; Geschichte; Geography, Medieval; Geography -- History -- 15th century; Cartography -- History; Early maps; Kartografie; Karte; Weltkarte